(untitled) (Journal of the Management Sciences, 2025)
The study examined the relationship between crisis management and organisational performance in Zenith Bank Plc in Awka metropolis. The specific objectives are to determine the relationship between information technology and employee productivity; to determine the relationship between crisis risk reduction and market share in Zenith Bank Plc in Awka metropolis. This study made use of descriptive survey research design. The study population comprised of 167 staff from selected Zenith Bank Plc branches in Awka metropolis. Census sampling technique was deployed in order to collect data from every member of the target group. Primary data were collected through a structured questionnaire distributed to the sampled participants. Test of hypotheses was done with the use of Spearman’s Rank Order Correlation, The Statistical Package for Social Sciences (SPSS) Version 23 was employed for these analyses. The findings include that information technology significantly and positively influences employee productivity of Zenith Bank Plc in Awka metropolis (rho = 0.449, p-value = 0.000). The study concludes that crisis management serves as a key mechanism for learning and adapting, allowing Zenith Bank to better prepare for future challenges and to align its resources and actions with its overarching objectives. Information Technology (IT) department of Zenith Bank Plc continues to invest in and enhance the bank’s technological infrastructure in order to support further improvements in employee productivity by providing advanced tools that facilitate better communication and operational efficiency.